Increasing the Income of the Mekar Mattirosompe Hydroponic Farmer Group through Solar-Powered Catfish and Vegetable Cultivation. - Achmad Fajar Muhammad Muhammad; Rahmatia Thahir Thahir; Nurlaela Nurlaela; Ahmad Swandi Swandi; Fina Melani Putri Putri (Universitas AMIKOM Yogyakarta, 2026)
The Community Partnership Program (PKM) aims to increase the income of the Mekar Hydroponic Farmers Group in Mattirosompe Village, Liukang Tupabbiring District, through the implementation of a solar-powered aquaponics system. By utilizing this technology, the farmer group is expected to overcome electricity constraints, increase agricultural productivity, and strengthen business management. The program also focuses on training in business planning and developing the managerial capacity of group members. The program's implementation results in increased production of water spinach, which can be harvested regularly, as well as good potential for catfish growth. Furthermore, the success of this program is expected to serve as a model for other farmer groups in the archipelago, supporting economic sustainability and awareness of the importance of renewable energy in the community. Through collaboration between universities and local communities, this program not only provides direct benefits but also builds a foundation for the development of modern, sustainable agriculture.